Nurses\' Attitude toward the Effect of Nursing Electronic Reports on Patient Care - Hassan BabaMohamadi; Mahdi Kahouie; Soheila Bayat; Sedigheh Fooladian; Maryam Shahsavane Toghan (Golestan University of Medical Sciences, 2013)
Background and Objective: ‌This study aimed to assess nurses' attitude toward the effect of nursing electronic reports on patient care. Material and Methods: This descriptive-analytical study was conducted on 316 nurses in the hospitals affiliated to Semnan University of Medical Sciences and social security organization, 2012.‌ The instrument was a researcher-made questionnaire,‌ valid and reliable. The data was analyzed by Chi Square, Fisher and Phi test. Results: Forty-seven five point percent of the nurses completely disagreed with the impact of electronic reporting on patient assessment‌ (1.8‌± 1.06) and 54.4% completely disagreed with its impact on the selection of clinical intervention (1.8 ± 1.06). On the other hand , 50% of nurses agreed with the effect of the computer program on patient care (2.2±0.99), 42.4% were satisfied with its effect on patient's diet planning (2.1±1.5) and 40.7% with the computer program on nursing diagnosis (2.01±1.09).There was significant relationship between some of the nurses' demographic characteristics and their attitude (P‌<0.05). Conclusion: Based on the results, nurses' attitudes can be attributed to some defects in the computer programs and to the nurses' compliance with information technology. To improve the effectiveness of electronic reporting, first, the quality of computer programs of clinical settings should be enhanced, and then changes should be occurred in organizational policies and in electronic documentation. Further, we should consider the impact of Levine's theory of change, indicating the staff's resistance to technology adoption in workplace.